Mutations in the TAR hairpin affect the equilibrium between alternative conformations of the HIV-1 leader RNA - Huthoff, Hendrik (Oxford University Press, 2001)
The HIV-1 untranslated leader RNA can adopt two mutually exclusive conformations that represent alternative secondary structures. This leader RNA can fold either an extended duplex through long-distance base pairing or a branched conformation in which the RNA locally folds into hairpin structures. Both leader RNA conformations have the TAR hairpin in common, which forms the extreme 5′ end of all HIV-1 transcripts. We report that truncation of the TAR hairpin shifts the equilibrium between the two RNA conformations away from the thermodynamically favored long-distance interaction. However, the equilibrium is partially restored in response to the cations Na(+) and Mg(2+). The transcripts with mutant TAR structures allowed us to investigate conditions affecting the competition between the alternative conformations of the HIV-1 leader RNA. We also demonstrate that the change in conformation of the leader RNA due to TAR truncations severely affects formation of the HIV-1 RNA dimer.